KAJIAN MENGENAI PERBURUAN PAUS PILOT (GRINDADRAP TRADITION) DI KEPULAUAN FAROE ATLANTIK UTARA BERDASARKAN INTERNATIONAL CONVENTION FOR THE REGULATION OF WHALING (ICRW) - Galuh Purborini (Faculty of Law Universitas Sebelas Maret, 2015)
Preservation and protection of the whale population is one of the main focus of international law enforcement. The threat of illegal whaling and illegal frequent in the interests of commercial and cultural traditions of a society or indigenous people. One species of whale that has endangered the existence is pilot whales continue to be hunted. Pilot whales diminishing its population due to hunting continuously by society Faroe Islands, the North Atlantic tradition carried to run each year, that tradition called Grindadrap tradition. Meanwhile , in fact there are International Convention For The Regulation of Whaling (ICRW) and the practical efforts undertaken by an international organization which is the International Whaling Commission (IWC). However, there is uncertainty existing regulations in the ICRW does not specifically regulate the ban on whaling and still allow the existence of a special permit (Special Permit) if the hunting and killing of whales deemed necessary. ICRW restore specific policies set by each country that Faroe Island authority of the state which is a region of Denmark. In fact Denmark has ratified ICRW in 1950. There is a failure to achieve an agreement between Denmark and the Faroe Islands led to Grindadrap tradition still occur which could threaten marine ecosystems until today.